IMPLEMENTASI REHABILITASI TERHADAP ANAK PENYALAH GUNA NARKOTIKA (Studi di Wilayah Kepolisian Daerah Lampung) - Ibrahim Fikma Edrisy (Fiat Justisia: Jurnal Ilmu Hukum, 2016)
Abstract The implementation of rehabilitation on underage narcotics users based on state regulation of narcotics, an addicts narcotics users is obliged to take a rehabilitation process, but this policy has never been applied, most of the underage narcotics users were sentenced to be put in jail than taking rehabilitation. The formulation of the problem in this thesis is: why is the implementation of rehabilitation on underage narcotics users so low. What is the problem with implementing rehabilitation on underage narcotics users? What do the police at Polda Lampung do on underage narcotics users? The result of the research show that the implementation of rehabilitation on underage narcotics users is not in line with state regulations, they are government policy, policy of health minister on technical regulation on medical rehabilitation for the drugs addicts, drugs users, and victim of drugs users, which stated that the underage narcotics users is supposed to be put in rehabilitation but this rule has never been applied on, most of the underage narcotics users were put in jail than on rehabilitation. The problem on rehabilitation is affected by some factors like law structure of Direktorat Narkoba Polda Lampung on the implementation of rehabilitation is not optimal, law culture on the level of obedience of the society about the law is not optimal, and the effort of Kepolisian Daerah Lampung in solving the underage narcotics users is through preemptive, preventive, and repressive way. Keywords: Rehabilitation, Under Age, NarcoticsAbstrak Pelaksanaan rehabilitasi pengguna narkotika di bawah umur berdasarkan peraturan negara narkotika, pengguna pecandu narkotika wajib mengambil proses rehabilitasi, tetapi kebijakan ini belum pernah diterapkan, sebagian besar narkotika di bawah umur pengguna dihukum untuk diletakkan di penjara daripada mengambil rehabilitasi. Rumusan masalah dalam skripsi ini adalah: mengapa pelaksanaan rehabilitasi pada narkotika pengguna di bawah umur sangat rendah. Apa masalah dengan melaksanakan rehabilitasi pada pengguna narkotika di bawah umur? Apa yang polisi di Polda Lampung lakukan pada pengguna narkotika di bawah umur? Hasil penelitian menunjukkan bahwa pelaksanaan rehabilitasi pada pengguna narkotika di bawah umur tidak sejalan dengan peraturan negara, mereka kebijakan pemerintah, kebijakan menteri kesehatan pada regulasi teknis rehabilitasi medis untuk pecandu obat, pengguna narkoba, dan korban narkoba pengguna, yang menyatakan bahwa pengguna narkotika di bawah umur seharusnya dimasukkan ke dalam rehabilitasi tapi aturan ini belum pernah diterapkan pada, sebagian besar pengguna narkotika di bawah umur yang dimasukkan ke dalam penjara dari pada rehabilitasi. Masalah rehabilitasi dipengaruhi oleh beberapa faktor seperti struktur hukum Direktorat Narkoba Polda Lampung pada pelaksanaan rehabilitasi tidak optimal, budaya hukum pada tingkat kepatuhan masyarakat tentang hukum tidak optimal, dan upaya Kepolisian Daerah Lampung dalam memecahkan pengguna narkotika di bawah umur adalah melalui cara preemptive, preventif, dan represif. Kata Kunci: Rehabilitasi, di Bawah Umur, Narkotika